How to Interpret Postoperative X‐rays after Total Knee Arthroplasty. Issue 3 (August 2014) - Kumar, Nishikant; Yadav, Chandrashekhar; Raj, Rishi; Anand, Sumit
<x xml:space="preserve">Abstract</x> Today, total knee arthroplasty (TKA) is one the most commonly performed surgeries worldwide. The purpose of this article is to review the appearance of normal post‐TKA roentgenographs and describe the correct sequence for their interpretation. It is unwise to depend solely on patients' symptoms when diagnosing TKA complications because serial radiographs can foresee failures well before they manifest clinically. Ideal post‐TKA radiographs comprise whole lower extremity anteroposterior and lateral views taken under weight bearing conditions along with a skyline view of the patellofemoral joint. Among other things, weight bearing exposes the true alignment, ligamentous laxity and polyethylene wear. On the basis of follow‐up of our TKA cases, we have drawn up a protocol for assessing postoperative X‐ray films after TKAs. Following the proposed sequence, surgeon can easily decide how to proceed with follow‐up and foresee complications. Careful interpretation of postoperative radiographs after TKA is essential to careful monitoring of patients and implant survival.